The approach to measuring the returns to secondary and tertiary qualifications in New Zealand : an investigation and update using data from the 2001 census : a research thesis submitted in fulfilment of the requirements for the degree of Master of Applied Economics at Massey University, Department of Applied and International Economics, College of Business, Massey University - Penny, Nathan J (Massey University, 2004)
This study investigates the approaches to measuring the returns to secondary and tertiary qualifications in New Zealand using the latest Census of Population and Dwellings data from 2001. It calculates the returns to qualifications using income function analysis, elaborate analysis and also extends the elaborate analysis by using the quantile regression technique. It reports returns within a narrow band for both methods and at a similar or higher magnitude to previous years. However, the results reported using the net present value (NPV) criteria reveal higher social returns to qualifications than private returns. This contradicts previous literature. In the policy implications section, the study recommends policies focus more on reducing the level of forgone earnings. Also, the study finds that income function analysis is better suited to measuring income inequality and its link with education. Furthermore, the study concludes that elaborate analysis, using the NPV criteria, allows better comparison of the marginal returns to educational investments of varying scale and duration. Finally, the quantile regression estimates show that point estimates of the mean return give a poor indication of the distribution of returns.
Keywords: New Zealand -- Econometric models; College graduates -- Employment; High school graduates -- Employment; Rate of return -- New Zealand; Income distribution -- New Zealand; Education, Higher -- Economic aspects; Education -- Economic aspects